Effects of dietary, salinity on the reproductive efficiency of mud clam broodstock (Austriella corrugata) in maturing condition - Thanh, Nguyen Xuan; Long, Luc Van; Trang, Tran Thi Thu; Hung, Pham Quoc (Vietnam Journal of Marine Science and Technology, 2019)
This study was conducted to evaluate the effect of dietary, salinity on the reproductive efficiency of mud clam broodstock (Austriella corrugata) in the maturing condition. The reproductive efficiency was assessed by survival rate, maturation rate, actual fecundity, spawning rate, fertilization rate, reproductive efficiency rate (100*D-veliger/fertilized eggs), larval quality. The experiment was held in the five dietaries and three salinities (18‰, 23‰ and 28‰). Three replicates were carried out for each treatment. Results showed that the reproductive efficiency of using fresh algae complex in 28‰ salinity was the highest and the larvae are in good quality, followed by that in the 23‰ salinity but having no statistically significant difference ( p > 0.05) while that in the 18‰ salinity experienced the least (p < 0.05). This study on dietary, salinity suggests that fresh algae complex in the salinity of 28 ± 1‰ is suitable for maturing broodstock of mud clam. These findings will contribute to building up hatchery production techniques as well as helping protection of natural stock and developing sustainable mud clam resource.